Effect of nutritional vitamin A deficiency on lipid metabolism in the rat heart: Its relation to PPAR gene expression - Vega, Verónica Analía (2009)
Objective: We studied the effect of dietary vitamin A deprivation on lipid composition and mRNA expression of regulatory enzymes involved in rat heart energetic lipid metabolism and its relation to the expression of peroxisome proliferator-activated receptor (PPAR) and retinoid X receptor (RXR) genes. Methods: Male Wistar 21-d-old rats were fed for 3 mo with a vitamin A-free diet (vitamin A-deficient group) and the same diet plus 8 mg of retinol palmitate per kilogram of diet (control group). One group of deficient animals received the control diet 15 d before sacrifice (vitamin A-refed group). Heart ventricular and mitochondrial lipid contents were determined. Lipid synthesis was measured using radioactive precursors and acetyl-coenzyme A carboxylase and mitochondrial carnitine palmitoyltransferase-I (CPT-I) activities using radioactive substrates. Fatty acid composition of mitochondrial phospholipids was analyzed by gas-liquid chromatography. Heart expression of acetyl-coenzyme A carboxylase, CPT-I, PPAR-α, PPAR-β, RXR-α, and RXR-β was assessed by reverse transcriptase polymerase chain reaction, and CPT-I expression was also measured by real-time polymerase chain reaction. Results: Vitamin A deficiency induced changes in heart ventricular lipid content and synthesis. Mitochondrial cardiolipin decreased and the proportion of phospholipids/saturated fatty acids increased. Heart activity and mRNA levels of CPT-I and expression of PPAR-α and PPAR-β genes were enhanced, whereas acetyl-coenzyme A carboxylase activity diminished. Furthermore, vitamin A deficiency decreased heart mRNA levels of RXRs. Vitamin A refeeding reverted most of the observed changes. Conclusion: Lipid metabolism is significantly modified in hearts of vitamin A-deficient rats. Alteration of mitochondrial energetic processes by modifying the activity and gene expressions of the regulatory enzymes is associated with a high PPAR expression induced by vitamin A deprivation.